Urogynecology: Introducing this Subspeciality for Managing Female Pelvic Floor Dysfunction in Nepal - Chaudhary, Pushpa (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i1.5051 NJOG 2010 Jul-Aug; 5(1): 1-2